PRODUKSI ENSIM KARBOKSI METIL SELULASE DAN EKSO-POLIGALAKTURONASE SERTA PERANANNYA DALAM MENENTUKAN TINGKAT PATOGENSITAS - MULYA, KARDEN; HENI, HENI; SUPRIADI, SUPRIADI; ADHI, ESTHER M. (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Carboxy methyl selulase and exo-polygalacturonase enzymes production and their role in determining the pathogenicity of Ralstonia solanacearum isolated from gingerBacterial wilt disease on ginger (Zingiber oicinale Roscoe) caused by Ralstonia solanacearum is the most destructive disease Infected tissues show macerated symptom on infected hosts indicating that the pathogen produces plant digestive enzymes. This research was aimed at analizing carboxymethylccllulasc (CMC-ase) and exopolygalacturonase (cxo-PG) enzymes production by the pathogen. In vitro production of CMC-ase of both virulent and avirulcnt isolates of R solanacearum was measured from diameter of clearing zone around bacterial colony on CMC medium whereas exo-PG was measured by the reduction of Na- polygalacturonatc by filtrate of the pathogen culture. Virulence of the pathogen was tested on tomato cultivar Gondol Hijau by pouring 50 ml of pathogen suspension (I07 cfu/ml) around roots of the plant and it was also tested on ginger cultivar Jahe Putih Besar by pricking suspension of pathogen into rhizome and basal pscudostcm of the plant. The results showed that CMC-ase and and PG-asc were produced by virulent isolates of R. solanacearum al 2.23 cm clear zone and 0.662 mg eq. glucose/ml/hour/ODiti, respectively. The avirulent isolates, however. correlated with disease intensity of the isolates. Disease intensity of the virulent isolates was 0.6 and 0.96 on tomato and on ginger plants respectively, whereas the avirulent isolates was 0.04 and 0.00 respectively. Therefore, CMC-ase and exo-PG are important in determining pathogenicity level of/?, solanacearum.